The Role of Protocol Section in Streamlining the Activities of Regional Heads (A Study at the Regional Secretariat of Padang Sidimpuan City) - Putri Marissa; Rudi Salam Sinaga; Maksum Syahri Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The role of the regional head in every event or activity of the regional government is very important, because the regional head is the highest leadership position in a region. The regional head as the highest leader in the region concerned must have control over all government activities, including all events held in the region. Protocol duties in the regions are carried out by the Protocol and Communication Section of the Regional Secretariat of Padangsidimpuan City. Therefore the authors are interested in conducting research in the form of a thesis with the title Role of the Protocol Section in Facilitating the Activities of Regional Heads (Studies at the Regional Secretariat of Padangsidimpuan City). The problems in this study are how the role of the protocol section in facilitating the activities of regional heads and the factors that become obstacles faced by the protocol in smoothing the activities of regional heads in Padangsidimpuan City. This study uses a qualitative approach, namely a problem-solving procedure that is investigated by describing the current state of the subject of the research object based on visible facts. The task of the regional protocol is to facilitate the implementation of regional government activities, namely planning activities, coordinating activities, carrying out activities and managing protocol documentation related to the activities of the regional head, in this case the Mayor of Padangsidimpuan. Meanwhile, the obstacle factors faced by the protocol section of the regional head's activities in the City of Padangsidimpuan are the lack of employee compliance with work discipline, the existence of a culture of unfair competition among employees, a poor evaluation system, and indecisive sanctions for violating regulations. It is suggested that the leadership of the protocol section need to emphasize to employees the importance of working time discipline so that it can support the smooth running of the activities of the regional head, which is accompanied by the provision of disciplinary sanctions for any violations.